(untitled) (Research, Society and Development, 2021)
Epigeal fauna are considered key biological indicators of soil quality, which can be used as parameters for determining sustainable agricultural production systems. This study aimed to evaluate the epigeal fauna under different monoculture and integrated production systems in a Yellow Latosol in the Cerrado biome. The epigeal fauna was sampled using pitfall traps in areas of no-tillage, pasture, exclusive eucalyptus cultivation, integrated livestock-forest system and in a native cerrado. The following variables were determined: number of individuals trap-1 day-1, total richness and the indices of Shannon and Pielou. The number of individuals trap-1 day-1 and richness were higher in native cerrado, while the no-tillage area presented the lowest values. For the Shannon and Pielou indices, native cerrado and integrated livestock-forest system presented the highest values while exclusive eucalyptus cultivation and no-tillage presented the lowest values. The pasture, exclusive eucalyptus cultivation and integrated livestock-forest system favored the ecological indexes of the epigeal fauna, while no-tillage was the system that least contributed to the establishment of these organisms. In areas explored with pasture, exclusive eucalyptus cultivation and integrated livestock-forest system, the community and the diversity of groups of fauna tend to increase. The association with different groups of fauna is more expressive in environments of native cerrado and exclusive eucalyptus cultivation.